Analysis of Customer Assessment of the Switching and Ease of Reserving Manual Transactions to Digital at Bank Syariah Indonesia KCP Medan Tomang Elok - Dela Setia; Ahmad Perdana Indra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Advances in technology today make it easy for all transactions. In fact, banking institutions such as Bank Syariah Indonesia are currently looking at the website as a means to apply online transaction reservations. Manual transactions are starting to be abandoned because they are considered less effective at this time. Bank Syariah Indonesia, especially Bank Syariah Indonesia Kcp Medan Tomang Elok has implemented an easy reservation method through the official digital web of Bank Syariah Indonesia. Digital transaction reservations are also considered easier for people of all ages to use. The purpose of this study is (1) to determine customer assessment of the manual to digital reservation method at Bank Syariah Indonesia Kcp Medan Tomang Elok. (2) Knowing the level of convenience in using the official digital web of Bank Syariah Indonesia by customers. To obtain these data, researchers used observation, interviews and documentation as data collection techniques. The data obtained from the research method was processed using qualitative descriptive analysis as the result of the research. Bank Syariah Indonesia Kcp Medan Tomang Elok has implemented the latest innovations to facilitate all customer transactions, so that transactions become faster and more efficient and minimize errors in manual data entry by customers..